Emission Reductions Significantly Reduce the Hemispheric Contrast in Cloud Droplet Number Concentration in Recent Two Decades. Issue 2 (12th January 2023) - Cao, Yang; Zhu, Yannian; Wang, Minghuai; Rosenfeld, Daniel; Liang, Yuan; Liu, Jihu; Liu, Zhoukun; Bai, Heming
Abstract: Anthropogenic activities have drastically impacted the climate system since the Industrial Revolution. However, to what extent anthropogenic emissions influence the cloud droplet number concentration ( N d ), the critical parameter for understanding aerosol‐cloud interactions, is poorly known on the hemispheric scale due to the considerable retrieval uncertainty. We employed multiple widely used N d retrieval sampling methods to evaluate the long‐term trend in N d contrast (Δ N d(NH‐SH) ) between the Northern Hemisphere (NH) and Southern Hemisphere (SH). Here we show that the Δ N d(NH‐SH) was halved from 2003 to 2020 using different sampling methods and channels, even though the range of magnitudes of Δ N d(NH‐SH) from different retrieval sampling methods is large. Such dramatic changes in Δ N d(NH‐SH) are dominated by the significantly decreased N d over the NH (∼20%) due to emission reductions compared to the relatively stable and pristine nature of the SH. Aerosol optical depth (AOD) and aerosol index (AI) correlate poorly with N d based on long‐term trends, even though they replicate the contrast trends. This poor correlation is partly contributed by stratospheric smoke from wildfires in Australia that had little influence on N d in the SH. The northwest Atlantic shows the largest contribution, ∼38%, to the N d trend, whereas the northwest Pacific dominates the change in AOD and AI, contributing more than 60% to AOD and ∼50% to the AI trend in the NH. Our results imply that emission reductions significantly reduced Δ N d(NH‐SH) and provide strong observational evidence that anthropogenic activities have extensively altered liquid clouds in the NH in the last two decades. Plain Language Summary: Cloud droplet number concentration ( N d ) is essential in understanding cloud physics, precipitation formation, and quantifying the effective radiative forcing associated with aerosol‐cloud interactions. Under the background of emission reductions over the past two decades, this study used global satellite observations to explore the long‐term (2003–2020) trend in N d over the ocean and its hemispheric contrast (Δ N d(NH‐SH) ) between the Northern Hemisphere and Southern Hemisphere. We found that N d decreased ∼20% over the Northern Hemisphere, but no clear N d trend was found over the Southern Hemisphere. As a result, the fractional change (defined as the trend divided by its climatology) of Δ N d(NH‐SH) is about −60% from 2003 to 2020. We further quantify the regional contribution and found that the northwest Atlantic shows the largest contribution, ∼38%, to the N d trend over the Northern Hemisphere. Our results provide strong observational evidence that anthropogenic activities have extensively modified the microphysical properties of liquid clouds in the Northern Hemisphere over the past two decades. Key Points: The interhemispheric contrast of cloud droplet number concentration ( N d ) was halved during 2003–2020 mainly due to emission reductions Although Aerosol optical depth (AOD) and aerosol index (AI) replicated the contrast trends, they correlate poorly with N d In the Northern Hemisphere, the northwest Atlantic contributes the most to N d long‐term change, whereas the northwest Pacific dominates the AOD/AI trend